Positive electrode material and preparation method thereof, lithium ion battery and electric device

By controlling the subgrain size and cobalt distribution of nickel-cobalt-manganese ternary cathode material, a structure with high cobalt on the surface and low cobalt inside is formed, which solves the problem of poor low-temperature performance of lithium iron phosphate material and realizes a lithium-ion battery with excellent low-temperature performance and low cost.

CN119133429BActive Publication Date: 2025-02-07BEIJING EASPRING MATERIAL TECH CO LTD

Patent Information

Application Number
CN202411586363.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-07
Publication Date
2025-02-07
Estimated Expiration
2044-11-07

AI Technical Summary

Technical Problem

Existing lithium iron phosphate materials have a low lithium-ion diffusion coefficient at low temperatures, resulting in poor charge and discharge performance. Improving the low-temperature performance of ternary materials increases costs and reduces market competitiveness.

Method used

By controlling the subgrain size distribution and cobalt concentration of the cathode material, a nickel-cobalt-manganese ternary material with low cobalt content is used, combined with an appropriate molar ratio of lithium source and cobalt source, to carry out a high-temperature solid-phase reaction, forming a particle structure with high cobalt on the surface and low cobalt inside, thereby improving lithium-ion transport performance.

Benefits of technology

It achieves excellent dynamic and low-temperature performance in low-temperature environments, while reducing material costs and improving the cycle performance and low-temperature discharge capability of lithium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119133429B_ABST
    Figure CN119133429B_ABST
Patent Text Reader

Abstract

The present application belongs to the field of battery technology and specifically discloses a positive electrode material and a preparation method thereof, a lithium ion battery and an electric device. The positive electrode material satisfies: 1.5<Kn 90 =(Ln 90 ‑Ln 10 ) / Ln 50 <4.5;0<Ln 10 <2000Å;Ln 10 <Ln 50 <3000Å;Ln 50 <Ln 90 <15000Å. The positive electrode material has high capacity, good cycle retention rate and excellent low-temperature performance, and the preparation method is simple to operate and low in cost. Using it in the battery is beneficial to improving the comprehensive performance of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the field of battery technology, and specifically relates to a positive electrode material and a preparation method thereof, a lithium-ion battery and an electrical device. Background Art

[0002] In recent years, lithium iron phosphate materials have dominated the domestic battery field due to their absolute cost advantages and good safety, and have broad development prospects. However, lithium iron phosphate materials themselves still have shortcomings: the polarity of phosphate is too strong, and the binding ability to lithium is too large, resulting in a low diffusion coefficient, which affects its charging and discharging performance in low temperature environments, making its low temperature performance, especially the performance under low battery charge (SOC) state, poor. In order to meet special application scenarios such as low temperature, some companies still choose higher-priced ternary materials to make batteries. Although the low-temperature performance of ternary materials is better than that of lithium iron phosphate materials, with the increasingly stringent market demand, the low-temperature performance of materials still needs to be further improved on the existing basis.

[0003] The diffusion coefficient of lithium ions in ternary materials decreases at low temperatures, and the energy required for charge transfer increases, which is manifested as high low-temperature impedance and poor low-temperature discharge capacity. In related technologies, low-temperature performance is improved by increasing the cobalt content or introducing solid electrolyte coating, but both methods will cause a significant increase in material costs, thereby reducing market competitiveness. Therefore, the low-temperature performance of positive electrode materials still needs to be further improved. Summary of the invention

[0004] The present application aims to solve at least one of the technical problems in the related art to a certain extent. To this end, the present application proposes a positive electrode material with high capacity, good cycle retention rate, excellent low temperature performance, simple operation or low cost, a preparation method thereof, a lithium ion battery and an electric device.

[0005] In a first aspect, the present application proposes a positive electrode material that satisfies:

[0006] 1.5<Kn 90 =(Ln 90 -Ln 10 ) / Ln 50 <4.5;

[0007] 0<Ln 10 <2000Å;

[0008] Ln 10 <Ln 50 <3000Å;

[0009] Ln 50 <Ln 90 <15000Å;

[0010] Among them, Ln 10 , Ln 50 , Ln 90 Kn is the sub-grain size corresponding to the cumulative percentage of the sub-grain size Ln of the positive electrode material reaching 10%, 50% and 90% respectively. 90 It is the subgrain size distribution of the positive electrode material.

[0011] In the positive electrode material, the subgrain size distribution is within the above range, which can effectively improve the dynamic performance and low-temperature performance of the positive electrode material.

[0012] In some embodiments, 500Å < Ln 10 <2000Å;2000Å<Ln 50 <3000Å;5000Å<Ln 90 <9000Å. The subgrain size within the above range is conducive to further improving the kinetic performance of the cathode material.

[0013] In some embodiments, 2.5 < Kn 90 <4.0. This is conducive to further improving the low temperature performance and kinetic performance of the positive electrode material.

[0014] In some embodiments, the particle size P satisfies 1.0 μm<P<2.0 μm; in other embodiments, 1.3 μm<P<1.7 μm. Within the above particle size range, it is beneficial for the particles to be completely sintered, thereby improving the conductivity and low temperature performance of the positive electrode material.

[0015] In some embodiments, the volume distribution median particle size of the positive electrode material is D'50, 1 μm<D'50<4 μm.

[0016] In some embodiments, the cathode material comprises a composition shown in Formula I:

[0017] Li 1+a (Ni x Co y Mn z G b )M c O 2 Formula I

[0018] Among them, 0≤a≤0.2, 0≤b≤0.05, 0≤c≤0.05, 0.4≤x<1, 0 <y<0.15,0≤z<0.5,

[0019] The element G includes at least one of Zr, Ti, Y, W, Al, Nb, and Sr;

[0020] The element M includes at least one of La, Zr, B, Nb, Ti, W, Si, Mg, and Al.

[0021] With the above chemical formula, the positive electrode material has a low cobalt content, low cost, and excellent low-temperature performance.

[0022] In some embodiments, the positive electrode material includes a substrate and a coating layer, wherein the coating layer is disposed on at least a portion of the surface of the substrate; and the element M is mainly located in the coating layer. Thus, the stability of the positive electrode material can be further improved, and when used in a lithium-ion battery, the side reaction between the positive electrode material and the electrolyte can be reduced, thereby facilitating the improvement of the cycle performance of the lithium-ion battery.

[0023] In some embodiments, the cobalt concentration on the surface of the positive electrode material particles is greater than the cobalt concentration inside the particles. By adjusting the cobalt concentration of the positive electrode material to form particles with high cobalt on the surface and low cobalt inside, the overall cobalt content in the positive electrode material can be relatively low while maintaining better low-temperature performance, thereby reducing costs.

[0024] In some embodiments, among all metal elements except lithium, the molar ratio of cobalt is greater than 0 and less than or equal to 15%, specifically greater than 0 and less than or equal to 10%, thereby reducing the content of cobalt and further reducing the cost.

[0025] The second aspect of the present application provides a method for preparing a positive electrode material, comprising:

[0026] Mixing a nickel-cobalt-manganese precursor and a lithium salt, and subjecting the obtained raw material mixture to a first sintering in an oxygen-containing atmosphere at 700° C. to 1000° C. for 6 h to 12 h to obtain an intermediate product;

[0027] The intermediate product, a lithium source and a cobalt source are mixed, and the intermediate product mixture is subjected to a second sintering in an oxygen-containing atmosphere at 300° C. to 800° C. for 6 h to 12 h to obtain the positive electrode material;

[0028] Wherein, the molar ratio of the lithium element in the lithium source to the cobalt element in the cobalt source is Y, and 0.5<Y<1.4.

[0029] The preparation method is simple to operate and low in cost. When the prepared positive electrode material is used in a battery, the low-temperature performance, kinetic performance and cycle performance of the battery can be improved.

[0030] According to an embodiment of the present application, the molar ratio of the lithium element in the lithium source to the cobalt element in the cobalt source is Y, 0.8<Y<1.2. Within the above ratio range, a lithium cobalt oxygen layer can be formed on the surface of the positive electrode material particles, increasing the cobalt content on the surface of the positive electrode material, thereby improving the lithium ion transmission performance and improving the low temperature performance.

[0031] According to the embodiments of the present application, the lithium salt includes at least one of lithium carbonate and lithium hydroxide; in some embodiments, the lithium salt includes a mixed lithium salt of lithium carbonate and lithium hydroxide; in some specific embodiments, the lithium salt includes a mixed lithium salt of lithium carbonate and lithium hydroxide with a lithium element molar ratio of 3:7 to 8:2. The use of mixed lithium salts can combine the advantages of the two lithium salts, allowing the single crystal particles to grow rapidly while maintaining good independence.

[0032] According to an embodiment of the present application, the molar ratio of the cobalt element in the cobalt source to the sum of the nickel, cobalt and manganese elements in the positive electrode material is less than 5%. Thus, the cobalt content on the surface of the positive electrode material can be increased, the lithium ion transmission performance can be improved, and the low temperature performance can be improved.

[0033] In some embodiments, the volume distribution median particle size of the nickel-cobalt-manganese precursor is D50, 1 μm<D50<3.5 μm.

[0034] The volume distribution median particle size D50 of the nickel-cobalt-manganese precursor is within the above range, which can reduce the adhesion between particles, so that the positive electrode material has a higher capacity and better low-temperature performance, and when it is used in a battery, the cycle performance of the battery can be improved.

[0035] In some embodiments, the raw material mixture further includes a compound containing element G.

[0036] In some embodiments, the intermediate mixture further includes a compound containing element M.

[0037] In some embodiments, the nickel-cobalt-manganese precursor includes at least one of nickel-cobalt-manganese oxide and nickel-cobalt-manganese hydroxide, so that the material source is wide and easy to obtain.

[0038] In some embodiments, the compound containing element G includes at least one of an oxide, a hydroxide, and a carbonate of the element G, and the element G includes at least one of Zr, Ti, Y, W, Al, Nb, and Sr. Thus, the material source is wide, which is conducive to improving the electrochemical performance of the positive electrode material.

[0039] In some embodiments, the cobalt source includes at least one of cobalt oxide, cobalt trioxide, cobalt oxyhydroxide, and cobalt hydroxide. Thus, the material source is wide, which is conducive to improving the low temperature performance of the positive electrode material.

[0040] In some embodiments, the lithium source includes at least one of lithium carbonate, lithium hydroxide, lithium phosphate, and lithium dihydrogen phosphate. Thus, the material source is wide and the cost is low.

[0041] In some embodiments, the compound containing element M includes at least one of an oxide, a hydroxide, and a carbonate of element M, and the coating element M includes at least one of La, Zr, B, Nb, Ti, W, Si, Mg, and Al. Thus, the material source is wide, which is conducive to improving the low temperature performance of the positive electrode material.

[0042] The third aspect of the present application provides a lithium-ion battery, comprising the positive electrode material described in the first aspect of the present application or the positive electrode material prepared by the method of the second aspect. Thus, the lithium-ion battery has low cost and excellent low-temperature performance.

[0043] The fourth aspect of the present application provides an electrical device, comprising the lithium-ion battery described in the third aspect of the present application. The electrical device has all the features and advantages of the lithium-ion battery described above, which will not be described one by one here. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] Figure 1 This is an electron microscope image of the finished positive electrode material of Example 1 of the present application.

[0045] Figure 2 This is an electron microscope image of the finished positive electrode material of Example 5 of the present application.

[0046] Figure 3 This is an electron microscope image of the finished positive electrode material of Example 6 of the present application.

[0047] Figure 4 This is an electron microscope image of the finished positive electrode material of Comparative Example 1 of the present application.

[0048] Figure 5 It is a subgrain size distribution diagram of the finished positive electrode materials of Example 1, Example 9 and Comparative Example 1 of the present application. DETAILED DESCRIPTION

[0049] The embodiments of the present application are described in detail below, and examples of the embodiments are shown in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present application, but cannot be understood as limiting the present application.

[0050] In a first aspect, the present application proposes a positive electrode material that satisfies:

[0051] 1.5<Kn 90 =(Ln 90 -Ln 10 ) / Ln 50 <4.5;

[0052] 0<Ln 10 <2000Å;

[0053] Ln 10 <Ln 50<3000Å;

[0054] Ln 50 <Ln 90 <15000Å;

[0055] Among them, Ln 10 , Ln 50 , Ln 90 Kn is the sub-grain size corresponding to the cumulative percentage of the sub-grain size Ln of the positive electrode material reaching 10%, 50% and 90% respectively. 90 It is the subgrain size distribution of the positive electrode material.

[0056] It should be noted that the subgrain size Ln of the positive electrode material is obtained by using the powder X-ray diffraction pattern obtained by using the CuKα ray powder X-ray diffraction measurement and the Fundamental Parameter method fitting algorithm to perform size statistics. 50 As a physical quantity representing the median value of the number distribution, it can represent the size of the sub-grain size. The smaller the sub-grain size, the shorter the migration path of lithium ions in the positive electrode material and the higher the diffusion rate, that is, the better the material kinetic performance. 90 It can reflect the uniformity of grain distribution. 90 If the subgrain size Ln is too large or too small, the conductivity of the material will deteriorate, the charge transfer impedance will increase, and the polarization will intensify, resulting in poor electrochemical performance of the material at low temperatures. 10 , Ln 50 , Ln 90 Out of range or Kn 90 If the requirements are not met, its low temperature performance will deteriorate to a certain extent.

[0057] In general, the subgrain size Ln 10 , Ln 50 , Ln 90 and Kn 90 When within the above range, the positive electrode material has excellent kinetic properties and low temperature properties.

[0058] In some embodiments, 500Å < Ln 10 <2000Å;2000Å<Ln 50 <3000Å;5000Å<Ln 90 <9000Å. In some specific examples, Ln 10 It can be 600Å, 800Å, 1000Å, 1200Å, 1400Å, 1600Å or 1800Å, etc. 50It can be 2100Å, 2200Å, 2300Å, 2400Å, 2500Å, 2600Å, 2700Å, 2800Å or 2900Å, etc. 90 It can be 5500Å, 6000Å, 6500Å, 7000Å, 7500Å, 8000Å or 8500Å, etc. The subgrain size within the above range is beneficial to further improve the kinetic performance of the positive electrode material.

[0059] In some embodiments, 2.5 < Kn 90 <4.0, specific, Kn 90 It can be 2.51, 2.6, 2.7, 2.8, 2.9, 3.0, 3.1, 3.2, 3.3, 3.4, 3.5, 3.6, 3.7, 3.8, 3.9, 3.99, etc. This is beneficial to further improve the low temperature performance and kinetic performance of the positive electrode material.

[0060] In some embodiments, the particle size P satisfies 1.0 μm<P<2.0 μm; in other embodiments, 1.3 μm<P<1.7 μm. In some specific examples, the particle size P may be 1.1 μm, 1.2 μm, 1.3 μm, 1.4 μm, 1.5 μm, 1.6 μm or 1.7 μm, etc.

[0061] It should be noted that the particle size P refers to the average diameter calculated by converting the projected area of ​​500 random particles into a standard circle of equal area through electron microscopy testing. If the particle size is too large, the lithium ion transmission path will increase, resulting in relatively poor electrical performance, which in turn leads to deterioration of the low-temperature performance of the particles; if the particle size is too small, the sintering may be incomplete, and the adhesion between the particles is relatively serious, which is not conducive to the formation of independent single crystal particles. Therefore, in order to obtain the best performance, the particle size can be controlled within a suitable range. Particle size within the above range is conducive to complete sintering of particles and improves the conductivity and low-temperature performance of the positive electrode material.

[0062] In some embodiments, the above-mentioned positive electrode material can be a single crystal nickel-cobalt-manganese ternary positive electrode material.

[0063] In some embodiments, the cathode material comprises a composition shown in Formula I:

[0064] Li 1+a (Ni x Co y Mn z G b )M c O 2 Formula I

[0065] Among them, 0≤a≤0.2, 0≤b≤0.05, 0≤c≤0.05, 0.4≤x<1, 0 <y<0.15,0≤z<0.5,

[0066] The element G includes at least one of Zr, Ti, Y, W, Al, Nb, and Sr;

[0067] The element M includes at least one of La, Zr, B, Nb, Ti, W, Si, Mg, and Al.

[0068] With the above chemical formula, the positive electrode material has a low cobalt content, low cost, and excellent low-temperature performance.

[0069] In some embodiments, the positive electrode material includes a substrate and a coating layer, wherein the coating layer is disposed on at least a portion of the surface of the substrate; and the element M is mainly located in the coating layer. Thus, the stability of the positive electrode material can be further improved, and when used in a lithium-ion battery, the side reaction between the positive electrode material and the electrolyte can be reduced, thereby facilitating the improvement of the cycle performance of the lithium-ion battery.

[0070] In some embodiments, the above-mentioned element G refers to an element with a deeper doping depth that can enter the interior of the particle, that is, a bulk doping element; and the element M is mainly located in the coating layer, which means that the element M is usually difficult to enter the crystal lattice of the positive electrode material, but is coated on the surface of the positive electrode material particles, or a small part of it diffuses into the interior of the positive electrode material particles near the surface.

[0071] In some embodiments, the cobalt concentration on the surface of the positive electrode material particles is greater than the cobalt concentration inside the particles. By adjusting the cobalt concentration of the positive electrode material to form particles with high cobalt on the surface and low cobalt inside, the overall cobalt content in the positive electrode material can be relatively low while maintaining better low-temperature performance, thereby reducing costs.

[0072] In some embodiments, among all metal elements except lithium, the molar proportion of cobalt is greater than 0 and less than or equal to 15%, specifically greater than 0 and less than or equal to 10%; for example, it can be 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9% or 10%, etc. In this way, the cobalt content can be reduced while maintaining a high low-temperature discharge capacity retention rate and a low low-temperature impedance, thereby further reducing production costs.

[0073] In this article, the description method used "particle surface" refers to the part of the positive electrode material particle from the outer surface to the inside, which accounts for 10% of the particle diameter, and "particle interior" refers to the part outside the above-mentioned particle surface.

[0074] In some embodiments, 10 detection points can be randomly selected on the particle surface and inside the particle by EDS to test the cobalt content, and then the average value 1 of the cobalt content at the particle surface detection points and the average value 2 of the cobalt content at the particle interior detection points are calculated. The average value 1 and the average value 2 represent the cobalt content on the particle surface and the cobalt content inside the particle, respectively.

[0075] The second aspect of the present application provides a method for preparing a positive electrode material, comprising:

[0076] S1: Mix a nickel-cobalt-manganese precursor and a lithium salt, and perform a first sintering on the obtained raw material mixture in an oxygen-containing atmosphere at 700°C to 1000°C (such as 700°C, 800°C, 900°C or 1000°C, etc.) for 6h to 12h (such as 6h, 7h, 8h, 9h, 10h, 11h or 12h, etc.) to obtain an intermediate product.

[0077] In some embodiments, the nickel-cobalt-manganese precursor includes at least one of nickel-cobalt-manganese oxide and nickel-cobalt-manganese hydroxide. The nickel-cobalt-manganese precursor used in the present application has an extremely low cobalt content. Although a cobalt source is added in subsequent steps, the cobalt content in the finished positive electrode material composition is still relatively low. This is beneficial for improving the low-temperature performance of the positive electrode material while reducing costs.

[0078] In some embodiments, the lithium salt includes at least one of lithium carbonate and lithium hydroxide. In some embodiments, the lithium salt includes a mixed lithium salt of lithium carbonate and lithium hydroxide. In other embodiments, the lithium salt includes a mixed lithium salt of lithium carbonate and lithium hydroxide with a lithium element molar ratio of 3:7 to 8:2; in some specific examples, the molar ratio of lithium elements in lithium carbonate and lithium hydroxide can be 3:7, 4:6, 5:5, 6:4, 7:3 or 8:2, etc.

[0079] It can be understood that during the sintering process of the positive electrode material, under the action of lithium salt and temperature, the primary fibers of the nickel-cobalt-manganese precursor will gradually grow and fuse to form multiple spherical adhesion particles. As the sintering time goes by, the adhesion particles will gradually grow, and the boundaries between the particles will gradually become obvious and finally separate to form multiple single crystal particles. The single crystal particles obtained by sintering pure lithium carbonate are easier to grow, and the adhesion is easy to separate, but the particle morphology is relatively irregular and the impedance is relatively high; the single crystal particles obtained by sintering pure lithium hydroxide have regular morphology and low impedance, but are relatively difficult to grow, and the adhesion is relatively difficult to separate, which may affect the high-temperature cycle performance; the use of mixed lithium salts can combine the advantages of the two lithium salts, so that the single crystal particles grow rapidly while maintaining good independence.

[0080] In some embodiments, the compound containing element G in this step may be added or not according to the needs of use. That is, when doping elements are not required, the raw material mixture in this step may only include nickel-cobalt-manganese precursor and lithium salt; when doping elements are required, the raw material mixture in this step includes nickel-cobalt-manganese precursor, lithium salt and a compound containing element G.

[0081] In some embodiments, the compound containing element G includes at least one of an oxide, a hydroxide, and a carbonate of the element G, and the element G includes at least one of Zr, Ti, Y, W, Al, Nb, and Sr. As some specific examples, the compound containing element G may be ZrO 2 , Y 2 O 3 or Al 2 O 3 Etc. This can play a role in bulk doping, thereby improving the electrochemical performance of the positive electrode material.

[0082] In some embodiments, the oxygen-containing atmosphere may be air or oxygen atmosphere, which may be flexibly selected according to actual needs.

[0083] In some embodiments, a crushing step is further included after the first sintering. Specifically, the crushing equipment is one or more of a soybean milk machine, a jaw crusher, a roller crusher, a colloid mill, a mechanical mill, and a jet mill. This can reduce the particle size of the intermediate product, which is beneficial for subsequent operations.

[0084] In some embodiments, the volume distribution median particle size of the nickel-cobalt-manganese precursor is D50, 1 μm<D50<3.5 μm. In some specific examples, D50 can be 1.5 μm, 2 μm, 2.5 μm or 3 μm, etc. Within the above range, the adhesion between particles can be reduced, so that the positive electrode material has a higher capacity and better low-temperature performance, and the cycle performance of the battery can be improved when it is used in the battery.

[0085] S2: mixing the intermediate product, a lithium source and a cobalt source, and subjecting the intermediate product mixture to a second sintering in an oxygen-containing atmosphere at 300°C to 800°C (such as 300°C, 400°C, 500°C, 600°C, 700°C or 800°C, etc.) for 6h to 12h (such as 6h, 7h, 8h, 9h, 10h, 11h or 12h, etc.) to obtain the positive electrode material.

[0086] In some embodiments, the lithium source includes at least one of lithium carbonate, lithium hydroxide, lithium phosphate, and lithium dihydrogen phosphate. Thus, the material source is wide and the cost is low.

[0087] In some embodiments, the cobalt source includes at least one of cobalt oxide, cobalt trioxide, cobalt oxyhydroxide, and cobalt hydroxide. Thus, the material source is wide, which is conducive to improving the low temperature performance of the positive electrode material.

[0088] In some embodiments, the molar ratio of the cobalt element in the cobalt source to the sum of the nickel, cobalt, and manganese elements in the positive electrode material is less than 5%, that is, n (cobalt in the cobalt source): n (the sum of nickel, cobalt, and manganese in the finished product) is less than 5%, for example, it can be 1%, 2%, 3%, or 4%, etc. This can reduce the cobalt content in the positive electrode material and reduce costs.

[0089] In some embodiments, the molar ratio of the lithium element in the lithium source to the cobalt element in the cobalt source is Y, 0.5<Y<1.4, in some specific embodiments, 0.8<Y<1.2. Specifically, the value of Y can be 0.6, 0.7, 0.8, 0.9, 1, 1.1, 1.2, 1.3, etc.

[0090] Among them, the addition of cobalt source and lithium source is to form a lithium cobalt oxide layer on the surface of the material by using a trace amount of cobalt, increase the cobalt content on the surface of the positive electrode material, thereby improving the lithium ion transmission performance and improving the low temperature performance. If the Y value is too low, the added cobalt source may not be able to fully react with lithium, the improvement effect is not ideal, and it may compete for lithium in the bulk phase, resulting in an increase in the lithium-nickel mixing of the material; if the Y value is too high, there may be too much residual lithium on the surface, and the processing performance and battery cycle performance are not ideal. When the Y value is within the above range, the low temperature performance of the positive electrode material can be effectively improved while basically not affecting other properties.

[0091] In some embodiments, the compound containing element M includes at least one of an oxide, a hydroxide, and a carbonate of element M, and the element M includes at least one of La, Zr, B, Nb, Ti, W, Si, Mg, and Al. As some specific examples, the compound containing element M may be Al 2 O 3 、TiO 2 or WO 3 Etc. As a result, the material source is wide, which is beneficial to improve the low temperature performance of the positive electrode material.

[0092] It should be noted that in this step, the compound containing element M may be added or not added according to actual needs. That is, when the compound containing element M is needed, the intermediate product, lithium source, cobalt source and the compound containing element M are mixed and sintered for the second time in this step; when the compound containing element M is not needed, the intermediate product, lithium source and cobalt source are mixed and sintered for the second time in this step. It can be understood that the positive electrode material may include a substrate and a coating layer provided on at least a portion of the surface of the substrate, and the element M is mainly located in the coating layer.

[0093] In some embodiments, the volume distribution median particle size of the positive electrode material is D'50, 1μm<D'50<4μm. In some specific examples, D'50 can be 1.5μm, 2μm, 2.5μm, 3μm or 3.5μm, etc. Within the above range, the adhesion between particles can be reduced, so that the positive electrode material has a higher capacity and better low temperature performance, and the cycle performance of the battery can be improved when it is used in the battery.

[0094] In some embodiments, the particle size increase rate X = (D'50-D50) / D50, and X < 0.25. Specifically, the particle size increase rate X can be 0.01, 0.05, 0.1, 0.15 or 0.2, etc. When the particle size increase rate is within the above range, the particle adhesion phenomenon is slight or even absent, which is beneficial to improve the electrical properties of the positive electrode material.

[0095] In some embodiments, (D'50-D50) / P<0.7, specifically, (D'50-D50) / P may be 0.65, 0.6, 0.55, 0.5, 0.45, 0.4, 0.35, 0.3, 0.25, 0.2, 0.15, 0.1, etc. Thus, the adhesion between particles can be reduced, and a positive electrode material with better low temperature performance can be obtained.

[0096] Among them, the volume distribution median particle size D50 and D'50 of the nickel-cobalt-manganese precursor and the positive electrode material are obtained by testing with a Malvern particle size analyzer. The single crystal particles prepared by the nickel-cobalt-manganese precursor with a smaller particle size have better independence and higher roundness, and have advantages in electrical properties (especially capacity and low temperature performance); and when the particle size P is equivalent, the difference between the D50 of the nickel-cobalt-manganese precursor and the D'50 of the single crystal nickel-cobalt-manganese ternary positive electrode material is within a suitable range, which can avoid serious adhesion of particles and help improve the cycle performance of the battery using the positive electrode material.

[0097] The method for preparing the positive electrode material of the present application is to mix a nickel-cobalt-manganese precursor with a low cobalt content with a lithium salt and an additive, and then use a high-temperature solid phase reaction to obtain an intermediate product, and then mix the crushed intermediate product with a lithium source, a cobalt source, and a compound, and then use a high-temperature solid phase reaction again to obtain a low-cobalt positive electrode material. Furthermore, in the preparation process, by controlling the type of lithium salt, the molar ratio of the lithium source to the cobalt source Y, the particle size P of the single crystal particles, the particle size increase rate X, and the parameters of the reaction conditions, the distribution of the sub-grain size in the positive electrode material is regulated, and the low-cobalt content The low-temperature performance of the positive electrode material is effectively improved.

[0098] The third aspect of the present application provides a lithium-ion battery, comprising the positive electrode material described in the first aspect of the present application or the positive electrode material prepared by the method of the second aspect. Thus, the lithium-ion battery has low cost and excellent low-temperature performance.

[0099] It can be understood that there is no particular limitation on the specific type of the lithium-ion battery, which can be a primary battery or a secondary battery; the shape of the lithium-ion battery can be a cylindrical battery, a square battery, or a battery of any other shape, etc., and according to the outer packaging classification, the lithium-ion battery can be a hard shell battery, a soft pack battery, etc.

[0100] Typically, a lithium-ion battery includes a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator, wherein the positive electrode sheet, the negative electrode sheet and the separator can be made into an electrode assembly by winding or lamination process, and the electrode assembly and the electrolyte can be contained in an outer package. During the charge and discharge process of the lithium-ion battery, active ions are embedded and released back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is arranged between the positive electrode sheet and the negative electrode sheet, which mainly plays the role of preventing the positive and negative electrodes from short-circuiting, and at the same time allows ions to pass through.

[0101] In some embodiments, the positive electrode sheet may include a positive electrode current collector and a positive electrode active material layer disposed on at least one side of the positive electrode current collector, the positive electrode active material layer includes a positive electrode active material, a conductive agent and a binder, and the positive electrode current collector may include a metal foil, for example, the metal foil may be an aluminum foil. The positive electrode active material may include the positive electrode material of the first aspect of the present application or the positive electrode material prepared by the method described in the second aspect of the present application. The conductive agent may include acetylene black, single-walled carbon nanotubes and conventional materials in the art. The binder may be polyvinylidene fluoride (PVDF) and conventional materials in the art.

[0102] In some embodiments, the negative electrode sheet may include a negative electrode current collector and a negative electrode active material layer disposed on at least one side of the negative electrode current collector. The negative electrode active material layer may include a negative electrode active material, a thickener, a conductive agent, and a binder. The negative electrode current collector may be a metal foil, for example, the metal foil may be a copper foil. The negative electrode active material may include artificial graphite, natural graphite, a silicon-containing carbon-based composite material, a lithium-containing metal composite material, a lithium metal material, and a common negative electrode active material in the art. The thickener may be a thickener sodium carboxymethyl cellulose (CMC-Na) and a conventional material in the art. The conductive agent may be acetylene black and a conventional material in the art. The binder may be styrene-butadiene rubber and a conventional material in the art.

[0103] In some embodiments, the separator can be a separator known in the art that can be used in lithium-ion batteries and is stable to the electrolyte used, such as a polyethylene separator, a polypropylene separator, a polyethylene / polypropylene composite separator, and the like.

[0104] The fourth aspect of the present application provides an electrical device, comprising the lithium-ion battery described in the third aspect of the present application. The electrical device has all the features and advantages of the lithium-ion battery described above, which will not be described one by one here.

[0105] In some embodiments, the electrical devices may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited to these.

[0106] The embodiments of the present application are described in detail below.

[0107] Example 1

[0108] (1) Preparation of single crystal nickel-cobalt-manganese ternary cathode material intermediate: Mix lithium carbonate and lithium hydroxide (the molar number of Li in lithium carbonate: the molar number of Li in lithium hydroxide = 7:3), nickel-cobalt-manganese hydroxide precursor (Ni 0.6 Co 0.05 Mn 0.35 )(OH) 2 (D50=2.72μm) and additive ZrO 2 The mixture is mixed evenly with a high-speed mixer in a molar ratio of 1.04:1:0.003; the mixture is then first sintered in an oxygen atmosphere at a sintering temperature of 970°C and a sintering time of 10 hours; after sintering, the sintered material is crushed with a jet mill to obtain a single crystal nickel-cobalt-manganese ternary positive electrode material intermediate;

[0109] (2) Preparation of single crystal nickel-cobalt-manganese ternary positive electrode material: The positive electrode material intermediate obtained in the above steps is mixed with the additive Al 2 O 3 , lithium source lithium carbonate, cobalt source Co(OH) 2 According to [n(Ni in the precursor) + n(Co in the precursor) + n(Mn in the precursor)] (can be abbreviated as [n(Ni) + n(Co) + n(Mn)]): n(Al 2 O 3 ):n(Li in lithium source):n(Co in cobalt source)=1:0.001:0.01:0.01 are mixed evenly by a high-speed mixer; the mixture is then subjected to a second sintering in an oxygen atmosphere, the sintering temperature is 700°C, and the sintering time is 8h; after sintering, the sintered material is crushed by a colloid mill to obtain a single crystal nickel-cobalt-manganese ternary positive electrode material product, D'50=3.08μm; specific indicators are shown in Table 1, and the electron microscope image is shown in Figure 1 .

[0110] Example 2

[0111] The difference from Example 1 is that in step (1), the first sintering temperature is adjusted to 987° C., and the other parameters remain unchanged, and the obtained finished product D'50=3.14 is obtained, as shown in Table 1.

[0112] Example 3

[0113] The difference from Example 1 is that in step (1), the composition of the nickel-cobalt-manganese precursor is adjusted to Ni:Co:Mn=60:10:30 (molar ratio), a precursor with D50=2.94 μm is used, and the finished product with D'50=3.44 μm is prepared by adjusting the colloid mill crushing strength, and the other parameters remain unchanged, as shown in Table 1.

[0114] Example 4

[0115] The difference from Example 1 is that in step (1), the lithium salt ratio is adjusted to: the molar number of Li in lithium carbonate: the molar number of Li in lithium hydroxide = 9:1, and the other parameters remain unchanged, and the finished product D'50 = 3.11 μm is obtained, as shown in Table 1.

[0116] Example 5

[0117] The difference from Example 1 is that the lithium salt in step (1) is adjusted to pure lithium carbonate, and the other parameters remain unchanged, and the obtained finished product D'50=3.04μm, as shown in Table 1, and the electron microscope image is shown in Figure 2 .

[0118] Example 6

[0119] The difference from Example 1 is that the lithium salt in step (1) is adjusted to pure lithium hydroxide, and the other parameters remain unchanged, and the obtained finished product D'50=3.08μm, as shown in Table 1, and the electron microscope image is shown in Figure 3 .

[0120] Example 7

[0121] The difference from Example 1 is that in step (1), the composition of the nickel-cobalt-manganese precursor is adjusted to Ni:Co:Mn=86:6:8 (molar ratio), D50=2.18 μm; the additive is in ZrO 2 Add Y 2 O 3 And lithium salt, nickel cobalt manganese precursor and ZrO 2 and Y 2 O 3 The addition ratio is adjusted to 1.03:1:0.002:0.001; the first sintering temperature is adjusted to 880°C, and the first sintering time is 8h;

[0122] The additive in step (2) is adjusted to TiO 2 , the lithium source is adjusted to lithium hydroxide, and the cobalt source is adjusted to Co 3 O 4 , [n(Ni in the precursor) + n(Co in the precursor) + n(Mn in the precursor)]: n(TiO 2):n(Li in lithium source):n(Co in cobalt source)=1:0.001:0.011:0.01; the second sintering temperature is adjusted to 650°C; the finished product D'50=2.74μm, and the other parameters remain unchanged, as shown in Table 1.

[0123] Example 8

[0124] The difference from Example 1 is that in step (1), the additive is in ZrO 2 Add Al 2 O 3 And lithium salt, precursor and ZrO 2 and Al 2 O 3 The addition ratio is adjusted to 1.05:1:0.002:0.001; the first sintering temperature is adjusted to 955°C, and the first sintering time is 12h; the finished product D'50=3.19μm, and the other parameters remain unchanged, see Table 1 for details.

[0125] Example 9

[0126] The difference from Example 1 is that the additive in step (2) is adjusted to WO 3 ,[n(Ni)+ n(Co)+ n(Mn)]:n(WO 3 ):n(Li in lithium source):n(Co in cobalt source)=1:0.001:0.01:0.01, and other parameters remain unchanged, and the finished product D'50=3.12μm is obtained, as shown in Table 1 for details.

[0127] Example 10

[0128] The difference from Example 1 is that in step (2), the cobalt source is adjusted to CoOOH, [n(Ni)+ n(Co)+ n(Mn)]: n(Al 2 O 3 ):n(Li in lithium source):n(Co in cobalt source)=1:0.001:0.007:0.01, and other parameters remain unchanged, and the finished product D'50=3.11μm is obtained, as shown in Table 1 for details.

[0129] Embodiment 11

[0130] The difference from Example 1 is that in step (2), the lithium source is adjusted to lithium phosphate, and the other parameters remain unchanged, as shown in Table 1.

[0131] Example 12

[0132] The difference from Example 1 is that: in step (1), the first sintering temperature is 965° C., and the first sintering time is 11 h;

[0133] In step (2), the additive M is adjusted to WO 3,[n(Ni)+ n(Co)+ n(Mn)]:n(WO 3 ):n(Li in lithium source):n(Co in cobalt source)=1:0.001:0.013:0.01, the second sintering temperature is adjusted to 620°C, the second sintering time is adjusted to 7h, and D'50=3.21μm is obtained by adjusting the crushing conditions; the other parameters remain unchanged, see Table 1 for details.

[0134] Comparative Example 1

[0135] The difference from Example 1 is that the amount of lithium source added in step (2) is adjusted so that [n(Ni)+ n(Co)+ n(Mn)]: n(Al 2 O 3 ): n (Li in lithium source): n (Co in cobalt source) = 1: 0.001: 0.003: 0.01, the other parameters remain unchanged, and D'50 = 3.18 μm is obtained, as shown in Table 1, and the electron microscope image is shown in Figure 4 .

[0136] Comparative Example 2

[0137] The difference from Example 1 is that the amount of lithium source added in step (2) is adjusted so that [n(Ni)+ n(Co)+ n(Mn)]: n(Al 2 O 3 ):n(Li in lithium source):n(Co in cobalt source)=1:0.001:0.01:0.005, and the other parameters remain unchanged, and D'50=3.07μm is obtained, as shown in Table 1 for details.

[0138] Comparative Example 3

[0139] The difference from Example 1 is that no lithium source is added in step (2), and the other parameters remain unchanged, and D'50=3.16 μm is obtained, as shown in Table 1.

[0140] Comparative Example 4

[0141] The difference from Example 1 is that in step (2), no cobalt source is added, and other parameters remain unchanged, and D'50=3.10 μm is obtained, as shown in Table 1.

[0142] Test and equipment:

[0143] (1) Particle size D50, D'50: measured by Marvern's Mastersizer 3000 laser particle size analyzer;

[0144] (2) Electron microscope test: obtained by scanning electron microscope S-4800 of Hitachi, Japan;

[0145] The projection area of ​​each single crystal particle in the electron microscope is counted, and then its particle size is obtained by calculation. The specific method is: the average diameter is calculated by converting the projection area of ​​500 random particles in the scanning electron microscope image into a standard circle of equal area, that is, the particle size P of the single crystal nickel-cobalt-manganese ternary positive electrode material;

[0146] (3) Ln 10 , Ln 50 , Ln 90 and Ni 2+ Molar content: tested by Rigaku rotating target diffractometer Smartlab 9KW, range 10-80°, voltage 40kv current 200mA step 0.02° scanning time 2° / min. The test results are obtained by statistically calculating the crystallite size using the WPPF grain size distribution function of SmartLabStudioII software according to the FundamentalParameter method (FP method). The sub-grain size distribution diagram of the finished positive electrode material of Example 1, Example 9, and Comparative Example 1 is shown in Figure 5 .

[0147] (4) Battery preparation and electrical performance testing:

[0148] In the above embodiments and comparative examples, the electrochemical performance of the single crystal nickel-cobalt-manganese ternary positive electrode material was tested using a CR2025 button cell, and the preparation process thereof is as follows:

[0149] Preparation of electrode sheet: The positive electrode material, conductive carbon black and polyvinylidene fluoride (PVDF) were mixed with an appropriate amount of N-methylpyrrolidone (NMP) in a mass ratio of 95:3:2 to form a uniform electrode slurry (with a solid content of 60% at 25°C). The slurry was coated on aluminum foil and dried at 120°C for 12 h. It was then stamped with a pressure of 100 MPa to form a positive electrode sheet with a diameter of 15.8 mm and a thickness of 3.2 mm. The loading amount of the positive electrode material was 15.5 mg / cm 2 In an argon-filled glove box with water and oxygen contents less than 5 ppm, the positive electrode, separator, negative electrode and electrolyte were assembled into a CR2025 button cell and left to stand for 6 hours. The negative electrode used a metal lithium sheet with a diameter of 15.8 mm and a thickness of 1 mm; the separator used a polypropylene microporous membrane (Celgard 2325) with a thickness of 25 μm; the electrolyte used 1 mol / L LiPF 6 A mixture of equal amounts of ethylene carbonate (EC) and diethyl carbonate (DEC).

[0150] Capacity test: The electrochemical performance of CR2025 button cells was tested using Shenzhen Xinwell Battery Test System, and the charge and discharge current density at 0.1C was 100 mA / g. The charge and discharge voltage range was controlled to be 3.0-4.4V. At room temperature, the button cells were charged and discharged at 0.1C to evaluate the charge and discharge specific capacity of the single-crystal nickel-cobalt-manganese ternary positive electrode material. Example 7 is a high-nickel material, and its test voltage range is 3.0-4.35V.

[0151] High temperature cycle performance test: In both the examples and comparative examples, the charge and discharge voltage range is controlled to be 3.0-4.4V. At a constant temperature of 60°C, the button cell is charged and discharged twice at 0.1C, and then charged and discharged 80 times at 1C to evaluate the high temperature cycle capacity retention rate of the single crystal nickel-cobalt-manganese ternary positive electrode material. Example 7 is a high nickel material, and its cycle test voltage range is 3.0-4.35V.

[0152] Low temperature performance test (all lithium-ion battery test voltage range is 3.0-4.4V):

[0153] The -10℃ low temperature capacity retention rate test is to activate the button cell by charging and discharging at 1C for one week at 25℃, record the discharge capacity A1 of 1C charge and discharge in the second week, transfer to -10℃ constant temperature box for 3h after full charge at 1C, and discharge at 1C, and record the discharge capacity as A2. The -10℃ low temperature capacity retention rate is A2 / A1×100%.

[0154] -10℃ 10% SOC-DCR test is to activate the button cell by charging and discharging at 1C for 1 week at 25℃, then charge to 10% SOC at 1C, transfer to -10℃ constant temperature box for 2h, and then discharge at 1C for 20s. -10℃ 10% SOC-DCR is (voltage at the last second of the shelf step - voltage at 20s of discharge) / discharge current.

[0155] -10℃ 20% SOC-DCR test is to activate the button cell by charging and discharging at 1C for one week at 25℃, then charge to 20% SOC at 1C, transfer to -10℃ constant temperature box for 2h, and then discharge at 1C for 20s. -10℃ 20% SOC-DCR is (voltage at the last second of the shelf step - voltage at 20s of discharge) / discharge current.

[0156] The low-temperature discharge capacity test is to activate the battery at 0.1C for one cycle (4.45V cut-off) at room temperature 25℃, then charge it at 0.5C to 10% SOC. Then transfer it to a -10℃ low-temperature cabinet, leave it for 1.5h, and discharge it at 0.5C to 3.0V. The time it takes to discharge to 3.0V is counted. The longer the discharge time, the stronger its low-temperature discharge capacity.

[0157] Table 1 Preparation process of examples and comparative examples

[0158]

[0159]

[0160] As shown in Table 2, Examples 1-12 all adjust the process parameters within the range allowed by the scheme, including the precursor nickel-cobalt-manganese composition, the type and amount of lithium salt added during the first sintering, the type of cobalt source and lithium source, the type of additives, etc., which can meet the purpose of this scheme to improve low-temperature performance (low-temperature capacity retention rate, low-temperature low SOC-DCR and low-temperature discharge capacity). However, due to the increase in sintering temperature, Example 2 sintered larger particle size, increased lithium ion transmission paths, and thus reduced capacity and increased low-temperature impedance. Compared with Examples 1 and 3, the cobalt content of the nickel-cobalt-manganese precursor in Example 3 is doubled compared with the cobalt content of the nickel-cobalt-manganese precursor in Example 1, but Ln 50 The low-temperature performance level is close to or even slightly worse than that of Example 1, indicating that the present solution has a more obvious effect on improving the performance of low-cobalt materials (especially low-temperature performance). Compared with Examples 1, 5, and 6, the electrical properties of the finished products prepared by using pure lithium carbonate or pure lithium hydroxide as lithium salt are slightly worse than those of the finished products prepared by mixing the two. In Example 5, pure lithium carbonate is used, which has a higher melting temperature and is more likely to react on the surface, and the prepared particle size will be larger (such as Figure 2 As shown, the lithium ion transmission capacity is poor, resulting in high impedance and poor low-temperature capacity retention rate; Example 6 uses pure lithium hydroxide with a low melting temperature, which has enough time to penetrate into the precursor, so that the positive electrode material particles grow from the inside to the outside, so the sintered particle size will be smaller and some particles will still be in a single crystal state (such as Figure 3 As shown in Figure 1), although the low temperature performance is better, the high temperature cycle life will be worse. Examples 8 and 9 are adjustments made from the aspects of doping and coating additives. The additive types and sintering conditions adjusted in Example 8 lead to Ln 50 The overall performance is better, but there is still a gap compared with Example 1; Example 9 only changes in the coating elements, so the performance is closer to Example 1, and it has excellent low-temperature performance. Example 10 adjusts the type of cobalt source and the lithium source to cobalt source ratio within the range allowed by the scheme. The performance of the prepared finished product is basically unaffected, but relatively speaking, when the lithium-cobalt ratio Y satisfies 0.8<Y<1.2, the low-temperature performance is better. Example 11 adjusts the lithium source lithium carbonate to lithium phosphate. Although the introduction of phosphate stabilizes the structure to a certain extent and has similar high-temperature cycle performance as Example 1, the lithium ion transmission capacity is limited, the capacity is slightly reduced, and the low-temperature DCR is also increased.

[0161] As shown in Comparative Examples 1 and 2, if the lithium-cobalt ratio is lower or higher than the range allowed by this scheme, it will affect the capacity, cycle, low temperature and other product performances: if the lithium-cobalt ratio is too low, the excess cobalt will consume the lithium in the positive electrode material particles, resulting in a decrease in the material capacity. At the same time, the lithium removal will increase the degree of lithium-nickel mixing, deteriorate the low temperature retention rate, and increase the low temperature impedance; if the lithium-cobalt ratio is too high, it will lead to excessive lithium, and a large amount of lithium will be enriched on the surface of the positive electrode particles, causing the material homogenization process to have problems such as slurry viscosity surge and jelly, and its high temperature cycle performance will also be greatly affected. Comparative Examples 3 and 4 do not add lithium source or cobalt source during the coating process, respectively, and the principle is the same as the limit conditions of the lithium-cobalt ratio in Comparative Examples 1 and 2.

[0162] The low temperature capacity retention rate and low temperature SOC-DCR both reflect the low temperature performance of the material. The higher the low temperature capacity retention rate, the lower the low temperature impedance, and the better the low temperature performance. The quality of low temperature performance can also be demonstrated by the low temperature discharge capability. In an environment where the temperature is too low, the energy of the battery is difficult to exert, and the discharge time is short. Therefore, the low temperature performance of the battery can be evaluated by the discharge time. The low temperature discharge capability law of the embodiment and the comparative example is consistent with the low temperature low SOC-DCR law.

[0163] The sub-grain size obtained by XRD refinement reflects that the size of the material grains can reflect the low-temperature variation law to a certain extent. In the above comparative examples and embodiments, the batches with high low-temperature discharge capacity retention rate and low low-temperature impedance all meet the Ln 10 <2000Å,Ln 50 <3000Å, and Kn 90 =(Ln 90 -Ln 10 ) / Ln 50 >1.5.

[0164] In the description of the present application, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Thus, a feature defined as "first" or "second" may explicitly or implicitly include at least one of the features. In the description of the present application, the meaning of "plurality" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined.

[0165] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0166] Although the embodiments of the present application have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limitations on the present application. Ordinary technicians in this field can change, modify, replace and modify the above embodiments within the scope of the present application.

Claims

1. A positive electrode material, characterized in that: satisfy: 1.5<Kn 90 = (Ln 90 - Ln 10 ) / Ln 50 <4.5; 0<Ln 10 <2000Å; Ln 10 <Ln 50 <3000Å; Ln 50 <Ln 90 <15000Å; Among them, Ln 10 , Ln 50 , Ln 90 Kn is the sub-grain size corresponding to the cumulative percentage of the sub-grain size Ln of the positive electrode material reaching 10%, 50% and 90% respectively. 90 is the subgrain size distribution of the cathode material; The positive electrode material comprises a composition shown in Formula I: Li 1+a (Ni x Co y Mn z G b )M c O₂ of formula I Among them, 0≤a≤0.2, 0≤b≤0.05, 0≤c≤0.05, 0.4≤x<1, 0 <y<0.15,0≤z<0.5, The element G includes at least one of Zr, Ti, Y, W, Al, Nb, and Sr; The element M includes at least one of La, Zr, B, Nb, Ti, W, Si, Mg, and Al.

2. The positive electrode material according to claim 1, characterized in that 500Å<Ln 10 <2000Å; 2000Å<Ln 50 <3000Å; 5000Å<Ln 90 <9000Å。 3. The positive electrode material according to claim 1, characterized in that 2.5<Kn 90 <4.0。 4. The positive electrode material according to claim 1, characterized in that The particle size P satisfies 1.0 μm<P<2.0 μm.

5. The positive electrode material according to claim 4, characterized in that 1.3μm<P<1.7μm.

6. The positive electrode material according to claim 1, characterized in that The volume distribution median particle size of the positive electrode material is D'50, 1 μm<D'50<4 μm.

7. The positive electrode material according to claim 1, characterized in that It comprises a substrate and a coating layer, wherein the coating layer is arranged on at least a part of the surface of the substrate; The element M is mainly located in the coating layer.

8. The positive electrode material according to claim 1, characterized in that The concentration of cobalt element on the surface of the particles of the positive electrode material is greater than the concentration of cobalt element inside the particles.

9. The positive electrode material according to claim 8, characterized in that Among all metal elements except lithium, the molar proportion of cobalt is greater than 0 and less than or equal to 15%.

10. The positive electrode material according to claim 8, characterized in that Among all metal elements except lithium, the molar proportion of cobalt is greater than 0 and less than or equal to 10%.

11. A method for preparing the positive electrode material according to any one of claims 1 to 10, characterized in that: include: Mixing a nickel-cobalt-manganese precursor and a lithium salt, and subjecting the obtained raw material mixture to a first sintering in an oxygen-containing atmosphere at 700° C. to 1000° C. for 6 h to 12 h to obtain an intermediate product; The intermediate product, a lithium source and a cobalt source are mixed, and the intermediate product mixture is subjected to a second sintering in an oxygen-containing atmosphere at 300° C. to 800° C. for 6 h to 12 h to obtain the positive electrode material; Wherein, the molar ratio of the lithium element in the lithium source to the cobalt element in the cobalt source is Y, and 0.5<Y<1.

4.

12. The method according to claim 11, characterized in that 0.8<Y<1.2。 13. The method according to claim 11, characterized in that The lithium salt includes at least one of lithium carbonate and lithium hydroxide.

14. The method according to claim 13, characterized in that The lithium salt includes a mixed lithium salt of lithium carbonate and lithium hydroxide.

15. The method according to claim 14, characterized in that The lithium salt comprises a mixed lithium salt of lithium carbonate and lithium hydroxide with a lithium element molar ratio of 3:7 to 8:

2.

16. The method according to claim 11, characterized in that The molar ratio of the cobalt element in the cobalt source to the sum of the nickel, cobalt and manganese elements in the positive electrode material is less than 5%.

17. The method according to claim 11, characterized in that The volume distribution median particle size of the nickel-cobalt-manganese precursor is D50, 1 μm<D50<3.5 μm.

18. The method according to claim 11, characterized in that Meet at least one of the following conditions: The raw material mixture also includes a compound containing element G; The intermediate mixture also includes a compound containing element M.

19. The method according to claim 18, characterized in that Meet at least one of the following conditions: The nickel-cobalt-manganese precursor includes at least one of nickel-cobalt-manganese oxide and nickel-cobalt-manganese hydroxide; The compound containing element G includes at least one of an oxide, a hydroxide, and a carbonate of the element G, and the element G includes at least one of Zr, Ti, Y, W, Al, Nb, and Sr; The cobalt source includes at least one of cobalt oxide, cobalt trioxide, cobalt oxyhydroxide, and cobalt hydroxide; The lithium source includes at least one of lithium carbonate, lithium hydroxide, lithium phosphate, and lithium dihydrogen phosphate; The compound containing element M includes at least one of an oxide, a hydroxide, and a carbonate of the element M, and the element M includes at least one of La, Zr, B, Nb, Ti, W, Si, Mg, and Al.

20. A lithium ion battery, characterized in that: The invention comprises the positive electrode material according to any one of claims 1 to 10 or the positive electrode material prepared by the method according to any one of claims 11 to 19.

21. An electrical device, characterized in that: Comprising the lithium ion battery as claimed in claim 20.

Citation Information

Patent Citations

  • Large-grain aggregate ternary positive electrode material and preparation method thereof, and lithium ion battery

    CN113716625A

  • Single-crystal type multi-element positive electrode material as well as preparation method and application thereof

    CN114703544A

Cited By

  • Positive electrode material and preparation method therefor, lithium-ion battery, and electrical device

    EP4773229A1

  • Positive electrode material and preparation method therefor, lithium-ion battery, and electrical device

    WO2026097681A1